Liming effect on the response and nitrogen symbiotic fixation of common bean (Phaseolus vulgaris L.). - García, Aurelio (2003)
Aglasshouse experiment was conducted in order to evaluate,using the A value method, the liming effect on the efficiencyof nitrogen symbiotic fixation (NSF) of the common beangenotypes BAT 58, BAT 477, DOR 364 and CC 25-9 (N) ina Rhodic Ferralsol soil. NN 125, a non nodulant commonbean, was used as the control crop. All common beangenotypes increased the fraction of N in plant derived fromsoil due to liming, mainly CC 25-9(N), that show a very lowcapacity to fix N from air if the soil is not amended with lime.Moreover, a beneficial effect of liming on the soil N pool wasfound, because the increasing total N uptake by plants wasdue to the N coming from the air, and the quantity of N inplant coming from the soil diminished, mainly for DOR 364and CC 25-9(N). In addition, the ratio %Ndff/%Ndfs, the Npercentage in plant derived from the fertilizer and derivedfrom the soil, respectively, vary due to the N percentageliming. Therefore, it is necessary to use two treatments for thecontrol in order to evaluate accurately the NSF: with andwithout the lime application. The Nitrogen Use Efficiencyparameter is disscused.